Rules of origin as commercial policy instruments - revisited. - VERMULST, Edwin A. (1992)
Argues that while rules of origin are an indispensible device to support the effectiveness of discriminatoy trade regimes, they have developed into a means of applying trade-restrictive measures where such restrictions do not necessarily follow from the application of other trade law instruments.